Caste-Continuity and Change in a Rural Community of Bangladesh (Bangladesh Journal of Public Administration, 2019)
Caste as a social and religious system has been undergoing changes over time. As we know caste is nothing but a mental situation of ‘Purity and Pollution’ which exhibit through different behavioral patterns of the people who have ascribed their status of socio-religious distinction. If we observe their behavioral patterns with intensity and apprehend the mental state behind those patterns, we find that the system still exists in a perishable manner. As ethnography, this study intends to explore the situational context of caste system in a Bangladesh village where both Hindus (Sanatana religion) and Muslims live together in separate residential areas. The study has designed to achieve some objectives through participated observation method in a village which is situated in Badarganj sub-district of Rangpur district. The both authors stayed in the village for fourteen months with two recesses. It was found that the present situation of caste system in the village has changed with the changes of the notions and attitude; the concept of untouchability has gradually weakened, but this can be the prediction that so long Hinduism persists, the concept of untouchability will endure. But, in general, the concept has been confined to the kitchen, and women have been the custodians of the concept. Regarding the changing pattern, we can say that caste, which was prevailing in a rigid form, is turning less rigid, and more flexible and adaptive in nature. It never was open, and never will be open like the class system.